A wearable solar-thermal-pyroelectric harvester: Achieving high power output using modified rGO-PEI and polarized PVDF. (July 2020) - Li, Haitao; Koh, Charlynn Sher Lin; Lee, Yih Hong; Zhang, Yihe; Phan-Quang, Gia Chuong; Zhu, Chao; Liu, Zheng; Chen, Zhensheng; Sim, Howard Yi Fan; Lay, Chee Leng; An, Qi; Ling, Xing Yi
Abstract: Harvesting solar energy via pyroelectric technology is highly desired because it is a sustainable and clean solution to yield electricity. However, the low power output (below 5mW/m 2 ) and bulky device design of traditional devices hinder their practical applicability. Herein, we demonstrate a highly efficient sunlight-triggered pyroelectric nanogenerator (S-PENG) design that achieves unprecedented performance of 21.3 mW/m 2 under one sun irradiation. This is achieved via enhancing both the solar harvesting properties and the pyroelectric efficiencies rationally by employing polyethyleneimine (PEI) chemically modified reduced graphene oxide (rGO-PEI), and a pyroelectric layer based on a polarized polyvinylidene fluoride (PVDF) film respectively. Moreover, we demonstrate its practical application by adapting the S-PENG into a wearable outdoor bracelet. Using a facile hand-waving motion to replace the traditional bulky sunlight-alternating device, our compact bracelet can charge a fitness tracker after only 1 h of outdoor exposure, demonstrating its capability to be seamlessly integrated with outdoor sports activities. We expect our rational design to promote the development of S-PENG and pave the way for the utilization of sunlight as a viable on-the-go electrical source. Graphical abstract: A wearable solar-thermal-pyroelectric harvester with high power output using modified rGO-PEI and polarized PVDF for solar energy harvesting has been demonstrated via leisure outdoor activity. The typical device as a viable on-the-go electrical source can directly charge smart electronic devices e.g., fitness tracker, demonstrating its capability to be seamlessly integrated with outdoor sports facilities. Image 1 Highlights: To demonstrate a rationally designed sunlight triggered pyroelectric nanogenerator (S-PENG) with high output (21.3 mW/m 2 ) consisted by a solar-thermal layer based on polyethyleneimine (PEI) chemically modified rGO (rGO-PEI), and a polarized polyvinylidene fluoride (PVDF) film sandwiched by Ag electrodes as the pyroelectric layer. To demonstrate an efficient solar-thermal layer based on chemically modified rGO using polyethyleneimine. To demonstrate a new wearable bracelet based on S-PENG for boosting the solar-light harvesting for charging modern electric devices.